Information Security Threats Encountered By Malaysian Public Sector Data Centers - Inthrani Shammugam; Ganthan Narayana Sam; Pritheega Magalingam; Nurazean Maarop; Bharanidharan Shanmugam; Sundresan A/L Perumal (Intelektual Pustaka, 2024)
Indexed by Scopus